Low glomerular filtration rate values are associated with higher TSH in an elderly population at high cardiovascular disease risk - Brenta, Gabriela; Nepote, Alejandra; Barreto, Adriana; Musso, Carla; Faingold, Cristina; Fossati, Pía; Antonelli, Alessandro; Fallahi, Poupak; Famá, Fausto; Meroño, Tomás (Frontiers in Endocrinology, 2023)
Background: Hypothyroidism is associated with impaired glomerular filtration rate (GFR), a recognized cardiovascular disease (CVD), and mortality risk factor. In older adults, this association remains unexplored. We aimed to determine the relationship of elevated TSH with GFR in an elderly population at high CVD risk.Methods: Older adults (age>65ys) with high CVD risk defined by two or more CVD risk factors: smoking (S), high blood pressure (HBP), high total cholesterol, low HDL cholesterol, diabetes (DM), metabolic syndrome or previous cardiovascular event, were prospectively included at our ambulatory Endocrine Clinic. Patients under levothyroxine or thyroid disease were excluded. TSH> 6mU/l defined subclinical hypothyroidism (ScH) with normal free T4 levels. Estimated GFR was calculated by the Berlin-Initiative Study (BIS)-1 formula for elderly population. Urinary albumin to creatinine ratio (uACR), IL-6 and TNF-α, and Carotid intima-media thickness (CIMT) were also determined. The U Mann-Whitney test, the Spearman test, and multiple linear regression were used as statistical tests, Results: Finally 246 patients (68% females) were included and 20 (8%) had ScH. This group, was older (median, Q1-Q3: 77,72-78; 72,68-77 years, p=0.01) and DM was less frequent than in the euthyroid group (35 vs 58%, p=0.039). Lower fasting glucose (-20%,p=0.01), GFR (-14%,p=0.01) and freeT4 (-10%,p<0.001) were found compared to euthyroid patients.A higher prevalence of Kidney failure was found in ScH (80 vs. 46%, p=0.003) vs. euthyroid individuals. Significant correlations with GFR were detected: age (r-0.482,p<0.001), TSH (r-0.172,p=0.004), IL-6 (r-0.150,p=0.047), TNF-α (r-0.274,p<0.001), uACR (r-0.170,p=0.009) and p=0.004). By multiple linear regression, in a model adjusted by age, sex, BMI, uACR, S, DM, TNF-α and HBP, TSH (Bst -0.14, p=0.023, R 2 =0.25) was found an independent predictor of GFR.In older adults with high CVD risk, ScH is associated with lower renal function, and this relationship is present regardless of other cardiometabolic risk factors. These results suggest that ScH could contribute to low GFR and excess CVD risk, although this hypothesis should be addressed in longitudinal studies.